Immutability Is Not Trust: Recourse, Reversibility, and the Patient at the End of the Chain - Nuno Filipe Galante Lourenco Goncalves Valério (Blockchain in Healthcare Today, 2026)
Blockchain promises records that can never be changed, and in healthcare this is often sold as a way to make data trustworthy. This piece argues that an unchangeable record solves only one part of the problem. It proves nobody altered the record after it was written. It does not prove the record was correct, say who is responsible for it, or let a patient challenge a decision that turns out to be wrong. Using data-integrity rules already standard in regulated medicine, the author argues that correcting mistakes and seeking a remedy are essential to the trust that blockchain in healthcare is meant to deliver. An unchangeable record proves only that data was not altered later, not that it was right to begin with. Trustworthy medical systems must let errors be corrected while keeping a permanent, attributed trail of each correction. Europe's right to erasure and the EU AI Act both assume records can change, and decisions can be contested. A permanent record of a wrong decision, that nobody can appeal, protects the record, but it does not protect the patient.